Idiopathic Brachial Neuritis Mimics Cervical Radiculopathy: A Case Report - (:unkn) unknown (GALENOS YAYINCILIK, 2020)
Idiopathic brachial neuritis (IBN) is an uncommon clinical disorder with an onset of acute, aching shoulder pain, followed by progressive muscle weakness and atrophy of the shoulder girdle and upper extremity. A 47-year-old male patient presented with an onset of acute left shoulder pain, which has lasted for two months. On physical examination, he also demonstrated a severe upper extremity weakness. Imaging tests showed a compression at C6 level on the left foramina! canal. According to these findings, the primary diagnosis was cervical radiculopathy, which may have required surgical intervention. However, the detailed history of pain, physical examination findings and electroneuromyography (ENMG) results were consistent with IBN that has a slow but progressive recovery with conservative treatment. Although a detailed history and physical examination are key points in the diagnosis of IBN, ENMG is the most helpful method for early and correct diagnosis that helps avoid unnecessary interventions.
Keywords: Brachial neuritis; cervical radiculopathy; electrophysiology; NEURALGIC AMYOTROPHY; DIAGNOSIS